Health-related quality of life and its socio-economic and cultural predictors among advanced cancer patients: Evidence from the APPROACH cross-sectional survey in Hyderabad-India - Jacob, J. (BioMed Central Ltd., 2021)
10.1186/s12904-019-0465-y